Konsepsi Ibnu Jarir Al-Tabari Tentang Al-Qur’an, Tafsir Dan Ta’wil - A.M Ismatulloh (FENOMENA, 2012)
The objective of this research is to describe the concept of Ibnu Jarir al-Tabari about al-Qur’an, tafsir and ta’wil. Ibn Jarir al-Tabari is an outstanding expert in the classic Islamic tradition. His knowledge in hadits, fiqh, lughah, history, and tafseer is unquestionable. This study uses an analytical descriptive design. The findings show that: Firstly, in defining al-Qur’an, al-Tabari focused on the al-Qur’an as an Arabic language text, not in other language. Secondly, al-Qur’an is written in sab’ah ahruf. It means that there are 7 different kinds of language with the same meaning. Thirdly, al-Qur’an comes from seven heaven’s door. Fourthly, there is no different word between tafseer and ta’wil. They have same meaning. These concepts are different to other concepts proposed by other ulama.